Strategi Operasi dalam Konteks: Lingkungan, dan Kinerja Perusahaan Industri di Sulawesi Selatan - Maat Pono (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
The background of research that performance of manufacturing industrial was influenced by operational strategy, environmental dynamic. The objective of research was to explain that: 1) Environmental dynamic influenced operational strategy, 2) Operational strategy influenced performance, 3) Environmental strategy has influence directly to performance. 4).Environmental strategy has influence indirectly to performance This research studied the relationship between variable so it was explanatory research. Site research was Makassar city, South Sulawesi with population target was large and middle industrial. The number of large and middle industrial population were 173 company at Makassar city. The samples used were 120 companies that those were widespread in all large and middle manufacturing industrial. Statistic analysis was used to examine hypothesis was path analysis. The result of research showed that: 1) Environmental dynamic influence operational strategic, 2) Operational strategic influenced performance, 3) Environmental dynamic has influence directly to performance. 4) Environmental dynamic has influence indirectly to performance.Keywords: industrial manufactory, environmental dynamic, operational strategic and performance.